Solar wind density control on the prompt penetration electric field and equatorial electrojet - Nilam, B.; Tulasiram, S.; Shiokawa, K.; Balan, N.; Zhang, Q. (My University, 2020)
Prompt penetration of convection/over shielding electric fields to equatorial and low latitudes during the southward/northward turnings of interplanetary magnetic field (IMF Bz) have been widely studied in the literature. The other types of penetration electric fields due to sudden changes in the solar wind dynamic pressure, IMF By and during the onset of sub storms have also been recently reported. In this paper, we present the exclusive role of solar wind density changes on the prompt equatorial electric field disturbances using the long‐term observations of equatorial electrojet (EEJ) from the Indian sector. In response to the sharp increases in the solar wind density, prompt increases/decreases in the EEJ indicating the eastward/westward prompt penetration electric field (PPEF) of ~20 min periods have been consistently observed on the dayside/nightside. The prompt equatorial electric field disturbances of the opposite polarity have also been observed when the density decreases sharply. Further, the polarity of these PPEF disturbances does not show any clear dependency on the direction of IMF Bz and By. This paper is the first report with a statistically significant number of observations on the characteristics of equatorial electric field disturbances in response to the sudden enhancements/decreases in the solar wind density alone on both day side and night side. The underlying physical mechanisms for the prompt equatorial electric field disturbances have been discussed in light of enhanced high‐latitude convection and additional field‐aligned currents due to sudden enhancement of solar wind density.
Keywords: Solar wind; PPEF; Prompt Penetration Electric Field; Equatorial Electrojet; EEJ